2023
DOI: 10.1111/joim.13755
|View full text |Cite
|
Sign up to set email alerts
|

Audiovisual gamma stimulation for the treatment of neurodegeneration

Cristina Blanco‐Duque,
Diane Chan,
Martin C. Kahn
et al.

Abstract: Alzheimer's disease (AD) is the most common type of neurodegenerative disease and a health challenge with major social and economic consequences. In this review, we discuss the therapeutic potential of gamma stimulation in treating AD and delve into the possible mechanisms responsible for its positive effects. Recent studies reveal that it is feasible and safe to induce 40 Hz brain activity in AD patients through a range of 40 Hz multisensory and noninvasive electrical or magnetic stimulation methods. Although… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 93 publications
1
2
0
Order By: Relevance
“…We found that 40 Hz multisensory audio-visual stimulation increased 40 Hz local field potential power in frontal cortex areas of 6-month-old 5XFAD mice (Extended Data Fig. 1a–c ), as expected on the basis of prior reports in mice 6 and humans 8 , 16 . In separate cohorts of 6-month-old 5XFAD mice, 40 Hz stimulation attenuated amyloid burden compared with no stimulation, 8 Hz stimulation and 80 Hz stimulation controls (Fig.…”
Section: Gamma Stimulation Promotes Glymphatic Clearancesupporting
confidence: 88%
See 2 more Smart Citations
“…We found that 40 Hz multisensory audio-visual stimulation increased 40 Hz local field potential power in frontal cortex areas of 6-month-old 5XFAD mice (Extended Data Fig. 1a–c ), as expected on the basis of prior reports in mice 6 and humans 8 , 16 . In separate cohorts of 6-month-old 5XFAD mice, 40 Hz stimulation attenuated amyloid burden compared with no stimulation, 8 Hz stimulation and 80 Hz stimulation controls (Fig.…”
Section: Gamma Stimulation Promotes Glymphatic Clearancesupporting
confidence: 88%
“…In humans and mice, sensory stimuli at specific frequencies can be used to promote neural activity corresponding to the sensory stimulation 15 . Noninvasive 40 Hz stimulation promotes 40 Hz neural activity in multiple brain regions, including the prefrontal cortex 6 , 7 , 16 , and we and others found that noninvasive 40 Hz sensory stimulation attenuates amyloid burden in Alzheimer’s disease model mice 8 . In particular, multisensory 40 Hz stimulation (that is, combined light and sound stimulation) attenuates amyloid burden throughout the cortex, including the prefrontal cortex 6 .…”
Section: Mainmentioning
confidence: 55%
See 1 more Smart Citation
“…Pulsed TES combined with periodic VS modulated gamma activity more strongly than the visual modality alone. This finding is highly relevant given the widespread interest in gamma stimulation to causally investigate associated cognitive functions such as memory (Hanslmayr et al, 2019), the role of gamma activity in general brain health (Başar, 2013), and new therapeutic avenues for neurodegenerative conditions, including Alzheimer’s Disease (Blanco-Duque et al, 2023). The present study opens the door for future research targeting higher neuronal frequencies with multimodal TES, VS, and EEG based on the optimised parameters determined here – i.e., occipital-central TES sites and matching stimulation frequencies.…”
Section: Discussionmentioning
confidence: 99%
“…By modulating gamma activity, both VS and TES at this frequency are promising approaches to causally investigate memory functions (Hanslmayr et al, 2019) and to intervene against cognitive decline in dementia (Guan et al, 2022;Nissim et al, 2023;Shu et al, 2024;Strüber & Herrmann, 2020;Traikapi & Konstantinou, 2021). If multisensory stimulation yields larger effects than one modality alone (Blanco-Duque et al, 2023), combining sensory and electrical modalities is also likely to increase effects, but this approach is untested. To examine how VS and TES might interact, it is necessary to measure brain activity concurrently.…”
Section: Introductionmentioning
confidence: 99%